Duodenal Laser Ablation for Treatment of Type 2 Diabetes: Results of First in Human Study - Kovarova, Viktorie; Lankova, Ivana; Machytka, Evzen; Knotkova, Katerina; Kratochvílová, Helena; Beneš, Marek; Spicak, Julius; Vasura, Adam; Goldin, Eran; Munter, Gavriel; Zima, Tomas; Mraz, Milos; et al. (United European gastroenterology journal, 2025)
BACKGROUND: Diabetes mellitus (DM) significantly impacts global health and economies. Despite various therapies, managing DM remains challenging. Bariatric surgery has shown efficacy in obese patients with type 2 diabetes mellitus (T2DM), but its utilization remains low. Innovative, less invasive endoscopic approaches such as duodenal mucosal resurfacing show potential in treating T2DM. This article presents the results of a First in Human (FIH) study using a duodenal submucosal laser ablation investigational device for T2DM treatment. METHODS: A prospective, single-arm, open-label study evaluated the safety and efficacy of the Digma System Endoscopic procedure for duodenal submucosal laser ablation in consecutive enrolled T2DM patients. RESULTS: The study was conducted from July 2017 to December 2020 and enrolled 31 patients for the Digma System Endoscopic procedure. The Dose Escalation Cohort (DEC) used sub-therapeutic laser doses for training and safety. The Treatment Cohort (TC) of 25 patients received therapeutic doses, resulting in HbA1c reductions of -0.6% at 6 months (p = 0.014) and -0.4% at 12 months (p = 0.062). Fasting glucose dropped 17.3 mg/dL (p = 0.173) at 6 months and 28 mg/dL (p = 0.022) at 12 months. Post-prandial glucose improvements were also observed. HOMA-IR improved at 3 and 6 months. PAGI-SYM and PAGI-QOL showed stable to slightly improved GI symptoms and quality of life. Two severe adverse events were unrelated to the procedure. CONCLUSION: The study demonstrates the safety, feasibility, and potential efficacy of the Digma System Endoscopic procedure. Evidence suggests improvements in HbA1c, fasting and post-prandial glucose, and HOMA-IR levels could be attributed to the Digma System Endoscopic procedure.
Keywords: dospělí; Intestinal Mucosa; Female; Quality of Life; Adult; výsledek terapie; ženské pohlaví; Diabetes Mellitus, Type 2; kvalita života; lidé; Blood Glucose; type 2 diabetes mellitus; diabetes mellitus 2. typu; Treatment Outcome; prospektivní studie; Male; Prospective Studies; Aged; duodenum; glykovaný hemoglobin; lidé středního věku; senioři; mužské pohlaví; Duodenum; laserová terapie; krevní glukóza; Middle Aged; Glycated Hemoglobin; Laser Therapy; metabolism; endoscopy; střevní sliznice; duodenal mucosal resurfacing; Humans